Rationalizations and identity conflict following smoking relapse: a thematic analysis. (2nd January 2017) - Wee, Lei Hum; Binti Ithnin, Azlyn Azmainie; West, Robert; Mohammad, Nihayah; Chan, Caryn Mei Hsien; Hasan Nudin, Siti Saadiah
Abstract: Introduction : Little is known about how smokers respond cognitively and emotionally to the experience of "late" relapse after the acute withdrawal phase. This study assessed the kinds of thoughts and feelings that emerge in order to provide a basis for quantitative research assessing prevalence of different types of response and implications for future quit attempts. Methods : Face-to-face in-depth interviews were conducted among 14 people attending a quit smoking clinic in Malaysia who had relapsed after at least 6 weeks of abstinence. Transcripts were analyzed using thematic analysis to enable emergence of important aspects of the experience. Results : Following relapse, smokers often engaged in rationalizations and activities to minimize worry about the harmful effects of smoking by switching to a lower-tar cigarette, reducing the number of cigarette smoked, attempting to reduce cigarette smoke inhalation, comparing themselves with other smokers, and minimizing the health risks associated with smoking. In some cases, smokers retained a "non-smoker" identity despite having relapsed. Conclusion : Smoking relapsers rationalize their failure to quit and minimize their health risk in order to protect their image as non-smokers while it remains a source of identity conflict.